Mental Role in Achievement of Koni's Pelatda Athletes Aceh Province in 2022 - Masyitah Masyitah; Amiruddin Amiruddin; Razali Razali; Hendra Nugraha; Miftah Fariz (universitas pgri palembang, 2023)
Mental has such an important role in the process of fostering athlete achievement. The purpose of this study was to find out the mentality of the Aceh Province KONI Foster Training Pelatda athletes in the face of PON XXI 2024 Aceh-North Sumatra. Athletes who are mentally tough are athletes who are able to stabilize their emotions in every performance then they can be ascertained stay on top of the game, and will never allow himself to be complacent. This research is a quantitative type . The sample in this study were the KONI Fostered Pelatda athletes Aceh Province, sampling using purposive sampling technique, amounting to 12 athlete. Data collection techniques using questionnaires and interviews. Research result as follows: of the 12 athletes of the Aceh Province KONI Foster Training Plate, 9 of them have mentally tough or mental level to compete they are at a high level with the percentage is 75% and 3 of them are in a state of moderate mental level the percentage is 25%, which means they have guts and level very good self-confidence both during training and competition. those results shows how the mental picture of the Aceh Province KONI Foster Pelatda athlete facing PON XXI 2024 Aceh-North Sumatra.